Prevalence and haematological parameters for bovine viral diarrhoea (BVD) in south Bengal areas in Bangladesh - Chowdhury, MMR; Afrin, F; Saha, SS; Jhontu, S; Asgar, MA (Bangladesh Veterinarian, 2016)
A total of 94 blood samples were collected from commercial dairy farms, from 6 Upazillas of Barisal division. The prevalence of Bovine Viral Diarrhoea Virus (BVDV) in south Bengal areas was 51.1%, the maximum prevalence was in Ujirpur Upazilla (Sub-district; 100%) and the lowest in Pirojpur Upazilla (13.6%). There was significant (P<0.05) variation in the prevalence between farms. Prevalence was highest (61.3%) in animals between 3 and 5 years of age, and lowest (31.8%) in 0-1 year-old animals. Animals with low body condition score (BCS-2) had higher (63.6%) prevalence in comparison to animals of high BCS-3.5. Haemoglobin (Hb) was 8.7 ± 0.1 gm% compared to 8.6 ± 0.1 gm%. Lymphocyte count was significantly (P<0.05) higher (64.1 ± 0.3%) in BVD-positive animals than negative animals (41.8 ± 1.2%). The neutrophil count was significantly (P<0.05) higher in BVD-positive animals (22.1 ± 0.5%) compared to negative animals (16.9 ± 0.5%). Other haematological parameters were not significantly different. Bangl. vet. 2015. Vol. 32, No. 2, 48-54